The Starch Is (Not) Just Another Brick in the Wall: The Primary Metabolism of Sugars During Banana Ripening - Cordenunsi-Lysenko, Beatriz Rosana; Nascimento, João Roberto Oliveira; Castro-Alves, Victor Costa; Purgatto, Eduardo; Fabi, João Paulo; Peroni-Okyta, Fernanda Helena Gonçalves (Frontiers in Plant Science, 2019)
The monocot banana fruit is one of the most important crops worldwide. As a typical climacteric fruit, the harvest of commercial bananas usually occurs when the fruit is physiologically mature but unripe. The universal treatment of green bananas with ethylene or ethylene-releasing compounds in order to accelerate and standardize the ripening of a bunch of bananas mimics natural maturation after increasing the exogenous production of ethylene. The trigger of autocatalytic ethylene production regulated by a dual positive feedback loop circuit derived from a NAC gene and three MADS genes results in metabolic processes that induce changes in the primary metabolism of bananas. These changes include pulp softening and sweetening which are sensorial attributes that determine banana postharvest quality. During fruit development, bananas accumulate large amounts of starch (between 15-35% w/w of their fresh weight, depending on the cultivar). Pulp softening and sweetening during banana ripening is attributed not only to changes in the activities of cell wall hydrolases but also to starch-to-sugar metabolism. Therefore, starch granules erosion and disassembling are key events that lead bananas to reach their optimal postharvest quality. The knowledge of the mechanisms that regulate sugar primary metabolism during banana ripening is fundamental to reduce post-harvest losses and improve final product quality, though. Recent studies have shown that ethylene-mediated regulation of starch-degrading enzymes at transcriptional and translational levels is crucial for sugar metabolism in banana ripening. Furthermore, the crosstalk between ethylene and other hormones including indole-3-acetic acid and abscisic acid also influences primary sugar metabolism. In this review, we will describe the state-of-art of sugars primary metabolism in bananas and discuss the recent findings that shed light on the understanding of the molecular mechanisms involved in the regulation of this metabolism during fruit ripening.